The roles of literature in the development of foreign language skills : the case of french language (2013)
The teaching of Literature in French in the Senior Secondary School Certificate Examination syllabus has spanned several decades in the Nigeria system of Education. It forms an integral part of the examination syllabus together with Essay and letter writing, Translation Lexis and structure, Dictation, Listening comprehension, reading of texts, conversation and cultural studies. A lot of controversies have trailed the continuous inclusion of French Literature into the examination syllabus at this level due to some problems encountered by students which include among others: lack of interest, language deficiency and non-availability of reading texts. Therefore, this paper sought to investigate the relative importance of literature to the development of language skills in the foreign language learning programme with particular interest in French language as the second official language in Nigeria. It was affirmed in this paper that literature helps in the training of the mind, (t serves as authentic materials for language learning and it motivates the learners because it is open to interpretation and gives room for drawing inferences from the reading texts. It was also concluded that the link between culture and language should not be over-emphasized in foreign language learning programme. Language competence and cultural competence are two essential skills in foreign language learning that could be treated in isolation without doing any arm to the acquisition of these skills.